The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4172/2162-6359.1000190
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Unlearning: An Analytical Literature Review

Abstract: This report sets out to provide an analytical review and commentary along the literature about unlearning in organizations (UO). Since this issue has managerial importance, this paper provides significant motivation for deepening our understanding of the unlearning. The review covers the period from 1981 to 2013 inclusive and focused on organizational management. Theoretical and empirical works are analyzed from the perspective of content focus. Three research themes are discussed: Antecedents (levels, process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Unlearning, considered to be the “intentional displacement of well-established patterns of action and understanding due to an exogenous disruption” (Fiol and O’Connor, 2017, p. 18), is contingent primarily upon two broad overarching catalysts: intentionality and subject-oriented components (Akhshik, 2014). As such, we contend that unlearning, the fulcrum catalyst of the learning process, must be a purposeful act and is not confined to subject-oriented factors such as organizational hierarchy, tenure or business units.…”
Section: Overview Of Unlearningmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlearning, considered to be the “intentional displacement of well-established patterns of action and understanding due to an exogenous disruption” (Fiol and O’Connor, 2017, p. 18), is contingent primarily upon two broad overarching catalysts: intentionality and subject-oriented components (Akhshik, 2014). As such, we contend that unlearning, the fulcrum catalyst of the learning process, must be a purposeful act and is not confined to subject-oriented factors such as organizational hierarchy, tenure or business units.…”
Section: Overview Of Unlearningmentioning
confidence: 99%
“…Together, these definitions provide a basis that unlearning refers to reducing the influence of prior knowledge and accepting that situational context is varied across the growth process. Referencing back to all definitions of unlearning by past scholars, four distinct themes routinely emerge: intentionality, process property, level-based definitions and subject-oriented methods (Akhshik, 2014). Of the four previously mentioned themes, intentionality and subject-oriented unlearning methods are perhaps the most beneficial and efficient within the field of HRD.…”
Section: Unlearning Definedmentioning
confidence: 99%
“…The "things" to which the definitions refer are, for the most part, knowledge and routines. In a review of 66 works on the unlearning literature (Akhshik, 2014), 43 and 19 per cent, respectively, dealt with the subjects of knowledge and routines. In this paper, we build on this understanding of unlearning as the process of discarding misleading knowledge and obsolete routines in organizations.…”
Section: Unlearning: Definition and Its Rolementioning
confidence: 99%
“…To reach the goal of organizational forgetting, it is crucial that adaptation and forgetting occur on the individual level (Kluge & Gronau, 2018). Individual forgetting is a precondition for organizational forgetting (Akhshik, 2014;Cegarra-Navarro & Moya, 2005), and similar to every human behavior, its success depends on various dispositional and situational factors (Niessen et al, 2020). For example, past research has shown that cognitive abilities are of particular importance for adaptation (e.g., Haase et al, 2020;Jundt et al, 2015).…”
Section: Introductionmentioning
confidence: 99%